2003
DOI: 10.1103/physreve.67.057102
|View full text |Cite
|
Sign up to set email alerts
|

Global persistence exponent of the two-dimensional Blume-Capel model

Abstract: The global persistence exponent theta(g) is calculated for the two-dimensional Blume-Capel model following a quench to the critical point from both disordered states and such with small initial magnetizations. Estimates are obtained for the nonequilibrium critical dynamics on the critical line and at the tricritical point. Ising-like universality is observed along the critical line and a different value theta(g)=1.080(4) is found at the tricritical point.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
57
2
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(69 citation statements)
references
References 29 publications
(44 reference statements)
9
57
2
1
Order By: Relevance
“…This critical temperature is slightly lower than that reported in Ref. 31, 2.13J / k B . At T c = 2.052J / k B , we compute a dynamic scaling exponent z using the nonequilibrium short-time dynamics of an initial configuration with total magnetization of zero at early times.…”
Section: B Equilibrium Propertiescontrasting
confidence: 48%
See 2 more Smart Citations
“…This critical temperature is slightly lower than that reported in Ref. 31, 2.13J / k B . At T c = 2.052J / k B , we compute a dynamic scaling exponent z using the nonequilibrium short-time dynamics of an initial configuration with total magnetization of zero at early times.…”
Section: B Equilibrium Propertiescontrasting
confidence: 48%
“…29 An expanded Bethe-Peierls approximation produced T c = 1.915J / k B , 30 and Monte Carlo simulations suggested that the critical temperature at H = 0 is 1.6950J / k B at D = 0 and 2.1855J / k B at D =5J. 31 In Ref. 31, nonequilibrium short-time dynamics at T c was studied using the heat-bath ͑Glauber͒ transition rate.…”
Section: A Dynamic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Using Monte Carlo simulations, many authors have obtained the dynamic exponents θ and z as well as the static ones β and ν, and other specific exponents for several models: Baxter-Wu [35], 2, 3 and 4-state Potts [36,37], Ising with multispin interactions [38], Ising with competing interactions [39], models with no defined Hamiltonian (celular automata) [40], models with tricritical point [41], Heisenberg [42], protein folding [43] and so on.…”
Section: B Non-equilibrium Critical Dynamicsmentioning
confidence: 99%
“…The sequence to determine the static exponents from short time dynamics is: first we determine z, performing Monte Carlo simulations that mixes initial conditions [36], and consider the power law for the cumulant…”
Section: B Non-equilibrium Critical Dynamicsmentioning
confidence: 99%